Dietary protocatechuic acid abrogates male reproductive dysfunction in streptozotocin-induced diabetic rats via suppression of oxidative damage, inflammation and caspase-3 activity (2019)
Clinical and experimental studies demonstrated that reproductive dysfunction is a non-lethal complication of diabetes. Protocatechuic acid (PCA) reportedly elicited several pharmacological effects in diabetic animals. However, there is paucity of information on the role of PCA in reproductive dysfunction associated with diabetes. The present study investigated the influence of PCA on the functional changes along the hypothalamicpituitary-testicular axis in male diabetic rats. Streptozotocin (STZ)-induced diabetic rats were orally treated with PCA at 25 and 50 mg/kg body weight for 45 consecutive days. Results showed that PCA treatment significantly dwindled blood glucose level as well as prevented diabetes mediated decrease in body weight gain and organosomatic indices of the testes and epididymis in the treated rats. Moreover, PCA increased the reproductive hormone levels, marker enzymes of testicular function and sperm functional characteristics in the treated rats. Further, PCA augmented the antioxidant status, inhibited lipid peroxidation and suppressed pro-inflammatory biomarkers including myeloperoxidase (MPO) activity, nitric oxide (NO) and tumor necrosis factor alpha (TNF-α) levels as well as caspase-3 activity inhypothalamus, testes and epididymis of diabetic rats. Collectively, PCA effectively abrogated reproductive deficits in diabetic rats via mechanisms involving suppression of oxidative stress, inflammation and caspase-3 activity along with enhancement of sperm functional parameters. Thus, PCA may preserve reproductive health in humans suffering from diabetes.